Magnetic field of Antarctic according to modelling calculations IGRF and supervision of observatories - Bakhmutov, V. G.; Yaremenko, L. N.; Melnyk, G. V.; Shenderovska, O. Ja. (Ukrainian Antarctic Journal, 2006)
The maps of components of the main magnetic field for 1960, 1995 and 2000 and its secular variations for epoch 1958 and 1997,5 for Antarctic, constructed on supervision on the Antarctic observatories with 1958 on 2003 and to modelling calculations of a magnetic field by IGRF coefficients are presented. The general reduction of intensity of a magnetic field in area of Antarctic, influence of Pacific focus of a century course on coast of Antarctica on longitudes 240–360° E and the big gradient of secular variations between the some rather closes located observatories is established.